Collective Action, Social Capital, and Household Empowerment in Farmer Cooperatives - Fayaz Gul Mazloum Yar; Bashir Ahmad Niazmal (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
Abstract. This study evaluates whether and how agricultural cooperative membership shapes multidimensional household empowerment in Nangarhar Province, Afghanistan. Objectives were to (1) estimate the Average Treatment Effect on the Treated (ATT) of cooperative membership on economic, social and political empowerment indicators, and (2) uncover mechanisms driving observed effects. Methods employed a convergent mixed-methods impact evaluation: a structured household survey of 420 households (210 cooperative members; 210 matched non-members) analyzed with one-to-one nearest-neighbor propensity score matching (caliper = 0.05) to estimate ATT and balance covariates, alongside 24 purposive in-depth interviews coded using a hybrid deductive–inductive approach in NVivo; scale reliability (Cronbach’s α > 0.78) and integration via joint displays were applied. Results show substantive gains for members: annual farm income (ATT = USD 128.45), access to microcredit (+12.8 percentage points), women’s household decision-making (+17.4 percentage points), and social-capital index (+0.65 points); qualitative evidence attributes these gains to strengthened social capital, peer mentoring, and collective bargaining. The cross-sectional design constrains causal inference beyond ATT estimates and suggests longitudinal or experimental follow-ups.